2018
DOI: 10.2337/db17-0134
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Reduces Severity of Aortic Aneurysms Depending on the Presence of Cell Division Autoantigen 1 (CDA1)

Abstract: Diabetes is a negative risk factor for aortic aneurysm, but the underlying explanation for this phenomenon is unknown. We have previously demonstrated that cell division autoantigen 1 (CDA1), which enhances transforming growth factor-β signaling, is upregulated in diabetes. We hypothesized that CDA1 plays a key role in conferring the protective effect of diabetes against aortic aneurysms. Male wild-type, CDA1 knockout (KO), apolipoprotein E (ApoE) KO, and CDA1/ApoE double-KO (dKO) mice were rendered diabetic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Although the direct impact of diabetes on biglycan expression in the aneurysmal aortic wall is still uncertain, diabetes is associated with an upregulation of Cell Division Autoantigen 1 (CDA1) which enhances TGF-β signalling pathway and contributes to the protective effect of diabetes on AAA formation. 37 DM can also alter the production, degradation and deposition of other GAGs in the aorta, with additional consequences on ECM remodelling as well as the structural and physical properties of the arterial wall. Decorin, a small leucin-rich repeat proteoglycan, is increased in response to high-glucose concentration, interacts with TGF-β to regulate matrix organization and collagen matrices and may reduce aneurysm formation in part through modulation of ECM remodelling.…”
Section: Mechanistic Effects Of Diabetes On Aortic Aneurysmmentioning
confidence: 99%
“…Although the direct impact of diabetes on biglycan expression in the aneurysmal aortic wall is still uncertain, diabetes is associated with an upregulation of Cell Division Autoantigen 1 (CDA1) which enhances TGF-β signalling pathway and contributes to the protective effect of diabetes on AAA formation. 37 DM can also alter the production, degradation and deposition of other GAGs in the aorta, with additional consequences on ECM remodelling as well as the structural and physical properties of the arterial wall. Decorin, a small leucin-rich repeat proteoglycan, is increased in response to high-glucose concentration, interacts with TGF-β to regulate matrix organization and collagen matrices and may reduce aneurysm formation in part through modulation of ECM remodelling.…”
Section: Mechanistic Effects Of Diabetes On Aortic Aneurysmmentioning
confidence: 99%
“…23,24 Hyperglycemia might influence angiogenesis, remodeling, extracellular matrix volume and glycation, advanced glycation end-products, inflammatory markers, oxidative stress, composition of the thrombus commonly present in an AAA, and transforming growth factor b signaling. [23][24][25] Furthermore, hemodynamic features of the aorta might differ between diabetic and nondiabetic patients, and computational fluid dynamic methods are currently evaluated to help understand such mechanisms. 26 Our methodology does not allow us to speculate about these mechanisms, however, as we have not assessed biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that CDA1 appears to be a significant molecule not only in DN but also in other diabetic vascular complications such as atherosclerosis [ 68 ]. Li et al [ 66 ] indicated that CDA1 plays a key role in the protective effect of diabetes on aneurysms. However, the specific mechanism by which CDA1 enhances the TGF- β signaling pathway and promotes renal fibrosis in DN deserves further investigation.…”
Section: Cda1 and Renal Fibrosis In Dnmentioning
confidence: 99%